Development of a pharmacy 'patient prioritization tool' for use in a Tertiary Paediatric Hospital. (22nd October 2020) - Spencer, Madeline; Turner, Sean; Garg, Alka
Abstract: What is known and objective: Pharmacists play an integral role in paediatric patient care by ensuring the safe and optimal use of medications. There are increasing demands on pharmacists' time and challenges to meet them within allocated resources, and therefore, it is important to ensure that resources are used efficiently. Patient prioritization tools for clinical pharmacists have been proposed via many studies, but are generally adult‐based and/or have not been validated to confirm their effectiveness. The aim of this study was to create, pilot and validate a patient prioritization tool to be used by pharmacists providing clinical pharmacy services to paediatric patients. Methods: A two‐phase (retrospective and prospective) observational audit of pharmacists' interventions collected via notes made on their ward handover information sheets and patient case notes was conducted over a 2‐year period in a tertiary paediatric hospital. A patient prioritization tool was created based on pharmacists' interventions in real time. This tool could be used at the start of the working day (without the need to review the patient or their case notes) to identify patients who would benefit most from a clinical pharmacist review. The tool was validated for effectiveness and selectivity. Results and discussion: The tool was easy to use and effective in identifying that 43% of paediatric inpatients did not require a routine clinical pharmacist review. It had 98% specificity in identifying patients who require a pharmacist intervention. It could be easily used at the start of the day to select patients for pharmacist review. What is new and conclusion: A new patient prioritization tool has been developed and validated for identifying paediatric inpatients requiring clinical pharmacist review. Abstract : A new paediatric patient prioritization tool based on real‐time pharmacists' interventions has been developed and validated. The tool is effective in identifying those higher‐risk patients who will benefit most from a pharmacist review.